AGRICULTURAL LENDING - Шалябин, Э.; Драхан, О. (SWorldJournal, 2021)
Regularities and tendencies of credit provision, estimation of influence of agrarian policy on a financial condition of the agricultural enterprises are investigated. Potential opportunities for agricultural producers to access bank loans are determined b